Whole genome sequencing and molecular epidemiology of paediatric Staphylococcus aureus bacteraemia. (June 2022) - Campbell, Anita J.; Mowlaboccus, Shakeel; Coombs, Geoffrey W.; Daley, Denise A.; Al Yazidi, Laila S.; Phuong, Linny K.; Leung, Clare; Best, Emma J.; Webb, Rachel H.; Voss, Lesley; Athan, Eugene; Britton, Philip N.; et al.
Abstract: Objectives: The role Staphylococcus aureus antimicrobial resistance genes and toxins play in disease severity, management and outcome in childhood is an emerging field requiring further exploration. Methods: A prospective multisite study of Australian and New Zealand children hospitalised with S. aureus bacteraemia (SAB) occurred over 24 months (2017–2018). Whole genome sequencing (WGS) data were paired with clinical information from the ISAIAH cohort. Results: 353 SAB isolates were sequenced; 85% methicillin-susceptible S. aureus ([MSSA], 301/353) and 15% methicillin-resistant S. aureus ([MRSA], 52/353). There were 92 sequence types (STs), most commonly ST5 (18%) and ST30 (8%), grouped into 23 clonal complexes (CCs), most frequently CC5 (21%) and CC30 (12%). MSSA comprised the majority of healthcare-associated SAB (87%, 109/125), with principal clones CC15 (48%, 11/21) and CC8 (33%, 7/21). Panton-Valentine leukocidin (PVL)-positive SAB occurred in 22% (76/353); predominantly MSSA (59%, 45/76), community-onset (92%, 70/76) infections. For community-onset SAB, the only microbiological independent predictor of poor outcomes was PVL positivity (aOR 2.6 [CI 1.0–6.2]). Conclusion: From this WGS paediatric SAB data, we demonstrate the previously under-recognized role MSSA has in harbouring genetic virulence and causing healthcare-associated infections. PVL positivity was the only molecular independent predictor of poor outcomes in children. These findings underscore the need for further research to define the potential implications PVL-producing strains may have on approaches to S. aureus clinical management.